Dispersion as a Survival Strategy - Junior, Valdivino Vargas; Machado, Fábio Prates; Roldán-Correa, Alejandro (Journal of statistical physics, 2016)
We consider stochastic growth models to represent population subject to catastrophes. We analyze the subject from different set ups considering or not spatial restrictions, whether dispersion is a good strategy to increase the population viability. We find out it strongly depends on the effect of a catastrophic event, the spatial constraints of the environment and the probability that each exposed individual survives when a disaster strikes.